Simbol dan Makna: Penyebaran Meme Narkoba dalam Instagram - Syahrul Akmal Latif; Henky Fernando; Yuniar Galuh Larasati (Jurnal Komunikasi, 2022)
In addition to describing drug abuse which was disseminated through meme symbols, this study also explained the meaning behind the emergence of drug meme symbols on Instagram. This study was a qualitative descriptive type using the netnography method. The data collection was carried out by analyzing 108 thousand meme symbols that were disseminated on the Instagram social media platform, using the hashtag search keyword #narkoba. The analysis was focused on themes, symbols, and languages used in the meme symbols. From these analysis, three most dominant classifications of meme symbol themes were selected and presented as findings in this study. This study utilized thematic analysis by emphasizing the development of themes or topics through drug meme symbols inductively, to reveal the meaning behind the drug meme symbols. The findings in this study indicated that drug abuse was widely disseminated through three meme symbols, namely latent dangers of drugs, law enforcement memes, social environment memes. In line with that, the use of the three meme symbol themes also referred to three critical, evaluative, and ideological meanings that became important findings in this study